Does the use of gonadotropin-releasing hormone antagonists in natural IVF cycles for poor responder patients cause more harm than benefit?. (2nd April 2016) - Aksoy, Senai; Yakin, Kayhan; Seyhan, Ayse; Oktem, Ozgur; Alatas, Cengiz; Ata, Baris; Urman, Bulent
Abstract: Poor ovarian response to controlled ovarian stimulation (COS) is one of the most critical factors that substantially limits the success of assisted reproduction techniques (ARTs). Natural and modified natural cycle IVF are two options that could be considered as a last resort. Blocking gonadotropin-releasing hormone (GnRH) actions in the endometrium via GnRH receptor antagonism may have a negative impact on endometrial receptivity. We analysed IVF outcomes in 142 natural ( n = 30) or modified natural ( n = 112) IVF cycles performed in 82 women retrospectively. A significantly lower proportion of natural cycles reached follicular aspiration compared to modified natural cycles (56.7% vs. 85.7%, p < 0.001). However, the difference between the numbers of IVF cycles ending in embryo transfer (26.7% vs. 44.6%) was not statistically significant between natural cycle and modified natural IVF cycles. Clinical pregnancy (6.7% vs. 7.1%) and live birth rates per initiated cycle (6.7% vs. 5.4%) were similar between the two groups. Notably, the implantation rate was slightly lower in modified natural cycles (16% vs. 25%, p > 0.05). There was a trend towards higher clinical pregnancy (25% vs. 16%) and live birth (25% vs. 12%) rates per embryo transfer in natural cycles compared to modified natural cycles, but the differences did not reach statistical significance.